Decision-making moon-bridge : SMEs’ usage of causation and effectuation perpetually in motion - Wathen, Pertti (Vaasan yliopisto, 2023)
The importance of new ventures and SMEs to the economy has been at the forefront of decision-making logic research. The growth and diversity of nascent effectuation have been reported in the literature, without forgetting the effects of the traditional causal approach. Despite the general popularity of the topic, literature on the role of decision-making logic in innovation, internationalization and business relationships is rather limited. To address this gap, this paper draws on causation and effectuation theories to develop: (1) a model that describes; (1a) the interconnectedness of the decision-making logics, (1b) matters that determine the prevailing logic, (1c) focus phenomena affected by decision-making logics, and (1d) how decision-making logic influences companies' reactions to opportunities and obstacles. (2) a concept that will assist entrepreneurs in their decision-making related considerations. The results are based on an abductive multi-case study on six Finnish energy technology firms, three of which are start-ups and three are solidly established SMEs. The main data were gathered through semi-structured interviews and observations within a time period of three years. The data indicate that these two logics are not opposites and most decisions contain at least the seeds of both logics. Actually, the findings confirm that the use of absolute causation or effectuation logic is negligible, and the usage of logics are intertwined and constantly changing. The contribution is a view of the decision-maker's role, the effects of the operational context and the subject matter topic on the definition of the prevailing decision-making logic and its effects.

Uusien yritysten ja pk-yritysten tärkeys taloudelle on ollut päätöksentekologiikan tutkimuksen kärjessä. Suhteellisen uuden toimintateorian (effectuation) vahvistumista ja monimuotoisuutta on kirjallisuudessa laajalti raportoitu, unohtamatta perinteisen kausaalisen (causation) lähestymistavan vaikutuksia päätöksen¬tekoon. Kuitenkin, huolimatta aiheen yleisestä suosiosta tutkimukset päätöksentekologiikan roolista innovaatioissa, kansainvälistymisessä ja liikesuhteissa on varsin rajallista. Tämän puutteen korjaamiseksi tämä tutkimus hyödyntää ”causation” ja ”effectuation” -teorioita kehittääkseen (1) mallin, joka kuvaa; (1a) päätöksentekologiikkojen keskinäistä yhteyttä, (1b) tekijöitä, jotka määrittävät vallitsevan logiikan (1c) fokusilmiöitä, joihin päätöksentekologiikat vaikuttavat ja (1d) miten päätöksentekologiikka vaikuttaa yritysten reaktioihin mahdollisuuksiin ja esteisiin. Lisäksi tutkimus hyödyntää näitä teorioita kehittääkseen (2) konseptin, joka auttaa yrittäjiä heidän päätösten tekoon liittyvissä pohdinnoissa. Tulokset perustuvat abduktiiviseen monitapaustutkimukseen kuudessa suomalaisessa energiateknologia-alan yrityksessä, joista kolme on startup-yrityksiä ja kolme vakiintuneita pk-yrityksiä. Merkityksellisin tutkimusdata kerättiin puolistrukturoiduilla haastatteluilla ja havainnoilla kolmen vuoden seurantajakson aikana. Tulokset osoittavat, että nämä kaksi logiikkaa eivät ole toistensa vastakohtia ja useimmat päätökset sisältävät molemmista logiikoista ainakin ituja. Itse asiassa havainnot vahvistavat, että absoluuttisen ”causation” tai ”effectuation” -logiikan käyttö on vähäistä ja toisiinsa kietoutuneiden logiikkojen käyttö on jatkuvassa muutoksessa. Tutkimuksen tuotos on selvä näkemys päätöksentekijän roolista sekä ympäristön, kontekstin ja itse aiheen vaikutuksista vallitsevaan päätöksentekologiikan ja näiden vaikutusten seurauksiin.
Keywords: entrepreneurship; decision making; small and medium-sized enterprises; enterprises; internationalisation; marketing; causativity; globalisation; business operations; entrepreneurs; fi=Kansainvälinen liiketoiminta|en=International Business|